Rethinking aid coordination - Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2011)
Should aid be better coordinated? And if so, how? The case for aid coordination is a powerful one. As aid poured into Haiti in the wake of a massive earthquake in January 2010, television coverage around the world broadcast two different realities. One story was about well-organized aid-givers collecting record donations and dispatching food and medical equipment by the tonne to Haiti. The other was a story about aid stymied by a lack of coordination. Television crews depicted Haitian families and children complaining that none of the food, medical assistance, or shelter was reaching them. The President of Haiti soon spoke out: "I am not in a position to criticize anybody, not in the least people who have come here to help me," Preval said. "What I am staying is, what everybody is saying is, that we need a better coordination."
Keywords: 330; Entwicklungshilfe; Politische Entscheidung; Internationale Beziehungen; Industrieländer; Entwicklungsländer